Pulmonary AVM: diagnosis via spiral CT scan: a case report - Hassan, Radhiana; Abdul Rahman, Zainun; Mohd Yusof, Mubarak (2009)
Pulmonary arteriovenous malformations (PAVMs) are abnormal communications between pulmonary arteries and pulmonary veins. It is a rare clinical problem.This case illustrates the use of spiral CT scan in diagnosing this condition.